LIFESTYLE AND ANTHROPOMETRIC INDICATORS HAVE GREATER ASSOCIATIONS WITH STEPS/DAY IN BOYS THAN IN GIRLS - Eduardo Rossato de Victo; Gerson Ferrari; Carlos André Miranda Pires; Dirceu Solé; Timóteo Leandro Araújo; Peter Todd Katzmarzyk; Victor Keihan Rodrigues Matsudo (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To verify the association of lifestyle, anthropometric, sociodemographic, family and school environment indicators with the number of steps/day in children. Methods: The sample consisted of 334 children (171 boys) from nine to 11 years old. Participants used the Actigraph GT3X accelerometer to monitor the number of steps/day, moderate to vigorous physical activity (MVPA) and sedentary time (ST) for seven consecutive days. Height, body weight, body mass index (BMI), waist circumference (WC), and body fat were also measured. Lifestyle indicators such as diet, environment, neighborhood, and parental schooling level were obtained with questionnaires. For the identification of variables associated to the number of steps/day, multiple linear regression models were used. Results: The mean steps/day of boys and girls were statistically different (10,471 versus 8,573; p<001). Among boys, the variables associated to the number of steps/day were: MVPA (β=0.777), ST (β=-0.131), BMI (β=-0.135), WC (β=-0.117), and BF (β=-0.127). Among girls, the variables associated to the number of steps/day were: MVPA (β=0.837), ST (β=-0.112), and parents' educational level (β=0.129). Conclusions: Lifestyle indicators, body composition variables and parental educational level influence the number of steps/day of children, and MVPA and ST are common for both sexes.